A kind of lignin-based conductive self-healing hydrogel and its preparation method and application

By using materials such as cyclodextrin, alkali lignin and polyvinyl alcohol in self-healing hydrogels, lignin-based conductive self-healing hydrogels are formed, which solves the problems of long self-healing time and poor mechanical strength, and achieves the effect of rapid healing and maintains good mechanical properties.

CN115286819BActive Publication Date: 2025-04-22JIANGSU UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211069362.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-02
Publication Date
2025-04-22
Estimated Expiration
2042-09-02

AI Technical Summary

Technical Problem

The existing self-healing hydrogels have a long time of self-healing, poor mechanical strength, difficult to heal quickly and maintain good mechanical properties.

Method used

By uniformly dissolving cyclodextrin, alkaline lignin and polyvinyl alcohol in the aqueous borax solution, adjusting the pH to alkaline, and freezing treatment, a lignin-based conductive self-healing hydrogel is formed. This method can heal quickly at room temperature, with healing time not exceeding 15 s and maintain mechanical properties.

Benefits of technology

The lignin-based conductive self-healing hydrogel that heals rapidly at room temperature (no more than 15 s) was achieved, and the mechanical properties did not decrease significantly after self-healing, and had good flexibility and mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115286819B_ABST
    Figure CN115286819B_ABST
Patent Text Reader

Abstract

The present invention relates to a lignin-based conductive self-healing hydrogel and a preparation method and application thereof, comprising the following steps: cyclodextrin, alkali lignin, and polyvinyl alcohol are uniformly dissolved in a borax aqueous solution to form a uniform mixture, then the pH value is adjusted to be alkaline to obtain a viscous material, and then a freezing treatment is performed to finally obtain a uniform and stable lignin-based conductive self-healing hydrogel; the mass ratio of the cyclodextrin, the alkali lignin, the polyvinyl alcohol, and the borax is 1:(0.5-3):3:(90-100). The self-healing hydrogel obtained by the method of the present invention can be quickly healed when placed at room temperature, the healing time does not exceed 15s, and there is no obvious decrease in mechanical properties after self-healing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a lignin-based conductive self-healing hydrogel and a preparation method and application thereof. Background Art

[0002] Lignin is the second largest biomass polymer on earth after cellulose. Lignin is a byproduct of the mass production of paper and the emerging cellulosic ethanol industry. Due to the large consumption of fossil fuels and their negative impact on the environment, lignin has been selected as a potential substitute for fossil fuel-based products. The unique structural properties of lignin give it unique characteristics, but due to its complex structure, the extraction and utilization of natural lignin are still difficult. At the same time, due to the charge effect of lignin, it agglomerates with other materials used to form larger particles, which hinders the performance of composite materials. Therefore, although more than 50 million tons of lignin are produced each year, less than 2% is used for value-added purposes, including concrete additives, stabilizers, dispersants and surfactants, and the rest is used as low-grade combustion fuel, resulting in a serious waste of lignin.

[0003] Hydrogel is a three-dimensional network polymer with a certain degree of cross-linking. Hydrogel molecules contain a large number of hydrophilic groups, have a strong affinity for water, can swell but not dissolve in water, and have a strong water retention capacity. Even under the influence of external factors such as squeezing and stretching, it can still maintain its internal water loss. In addition, due to its unique physical and chemical properties, such as adjustable mechanical properties, softness, low friction coefficient, and high plasticity, hydrogel has been widely used in drug controlled release, soft tissue engineering, materials, wastewater treatment, sensors, artificial skin and other fields in the past decade.

[0004] Self-healing materials are an emerging type of material that can recognize damage and self-repair. Researching, developing and applying the self-healing properties of materials can greatly improve the service life of materials, reduce resource consumption and costs, and have considerable economic and environmental benefits. Therefore, it is very necessary to develop environmentally friendly, clean, widely available and sustainable self-healing biomaterials. In the self-healing hydrogel material system, reversible chemical reactions make the generated covalent bonds present a dynamic reversible formation and breaking mechanism. Common dynamic covalent bonds include disulfide bonds, phenylboronate bonds, heterocyclic bonds and DA reactions. The method for preparing self-healing hydrogels based on the dynamic boron ester bonds formed between polyvinyl alcohol and borax is simple and has also been widely studied. However, the hydrogels produced all show defects such as long self-healing time, insufficient strength and poor mechanical properties. Therefore, a simple method for preparing fast-healing lignin-based self-healing conductive hydrogels has important practical significance. Summary of the invention

[0005] In order to solve the technical problems of long self-healing time and poor mechanical strength of self-healing hydrogel, a lignin-based conductive self-healing hydrogel and its preparation method and application are provided. The self-healing hydrogel obtained by the method of the present invention can heal quickly at room temperature, the healing time does not exceed 15s, and the mechanical properties do not decrease significantly after self-healing.

[0006] In order to achieve the above objectives, the present invention is implemented by the following technical solutions:

[0007] A method for preparing a lignin-based conductive self-healing hydrogel comprises the following steps:

[0008] The cyclodextrin, alkaline lignin and polyvinyl alcohol are uniformly dissolved in a borax aqueous solution to form a uniform mixture, and then the pH value is adjusted to be alkaline to obtain a viscous material, which is then frozen and thawed to room temperature to finally obtain a uniform and stable lignin-based conductive self-healing hydrogel;

[0009] The mass ratio of the cyclodextrin, the alkali lignin, the polyvinyl alcohol and the borax is 1:(0.5-3):3:(90-100).

[0010] Furthermore, the cyclodextrin is one or more of α-cyclodextrin, β-cyclodextrin, and γ-cyclodextrin; the molecular weight of the polyvinyl alcohol is 15,000-20,000; and the mass concentration of the boric acid aqueous solution is 0.5-2%.

[0011] Furthermore, adjusting the pH value to be alkaline means adjusting the pH value of the mixture to 8-10. Only under alkaline conditions can polyvinyl alcohol and borate form a cross-linked structure.

[0012] Furthermore, the freezing treatment temperature is -20 to 10°C and the treatment time is 12 hours. The freezing treatment can "freeze" the motion state of the PVA molecular chains in the aqueous solution at a certain moment, so that the contacting molecular chains can interact and entangle, and are tightly combined through physical effects such as van der Waals forces and hydrogen bonds, and are not separated in a certain micro-region and thus become "entanglement points"; refreezing will occur during the freezing treatment time, and refreezing will form new ordered micro-regions, which are called "physical cross-linking points". In the freezing-thawing process, the movement of molecular chain segments can be promoted and rearranged, and a hydrogel with a semi-crystalline or crystalline structure can be obtained by folding the molecular chains, which greatly improves its physical properties and mechanical properties.

[0013] Another aspect of the present invention provides a lignin-based conductive self-healing hydrogel prepared by the above method.

[0014] The last aspect of the present invention provides the use of the lignin-based conductive self-healing hydrogel prepared by the above method in wearable electronic sensors, which are applied to wearable electronic sensors for fingers, wrists, and elbow joints.

[0015] Beneficial technical effects:

[0016] 1. The lignin-based conductive self-healing hydrogel prepared by the present invention forms a double cross-linked network under the interweaving of the rigid network of lignin and cyclodextrin and the flexible network of polyvinyl alcohol. It has good flexibility, can control its shape at room temperature, can restore its original shape within 8 seconds at room temperature, and has good mechanical properties. It can withstand various deformations, such as bending and elongation, and can be stretched to 20 times its original length without breaking.

[0017] 2. The lignin-based conductive self-healing hydrogel prepared by the present invention can automatically repair mechanical damage in the gel without using a healing agent and without external stimulation, inhibit the propagation of damage, restore the integrity of the network, extend the service life of the material, significantly improve the material safety, and optimize the economic benefits; it only needs to contact the cut surfaces together at room temperature to automatically combine, and after 8 seconds of contact, the interface self-repairs completely and merges into a whole, and the interface completely disappears. Compared with the original hydrogel, the tensile properties of the hydrogel that has healed again after cutting are almost not reduced.

[0018] 3. The lignin-based conductive self-healing hydrogel prepared by the present invention does not require the addition of piezoelectric carbon materials, etc. The obtained lignin-based conductive self-healing hydrogel has good conductivity and strain sensing sensitivity, and high conductivity recovery efficiency, and can be used to monitor joint movement.

[0019] 4. The method of the present invention is simple and easy to implement, does not require expensive equipment, has a wide source of raw materials, is low in cost, is green and environmentally friendly, and is renewable. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is an infrared spectrum of the lignin-based conductive self-healing hydrogel prepared in Example 2; wherein 1% LCP represents the product of Example 2, 0% LCP represents the product of Comparative Example 2, CP represents the product of Comparative Example 1, AL powder represents the raw material alkali lignin powder, PVA powder represents the raw material PVA powder, and β-CD powder represents the raw material β-cyclodextrin.

[0021] Figure 2 This is a SEM image of the cross section of the lignin-based conductive self-healing hydrogel prepared in Example 2.

[0022] Figure 3 It is an isothermal frequency scanning curve diagram of the lignin-based conductive self-healing hydrogels of Examples 1-3 and the hydrogel of Comparative Example 2.

[0023] Figure 4 This is the actual picture of lignin-based conductive self-healing hydrogel after 1% LCP stretching.

[0024] Figure 5 Self-healing time-efficiency diagram of lignin-based conductive self-healing hydrogel.

[0025] Figure 6 The diagram is a formation mechanism diagram of lignin-based conductive self-healing hydrogel according to the method of the present invention, wherein the term Lignin refers to lignin, PVA refers to polyvinyl alcohol, β-CD refers to β-cyclodextrin, and Hydrogen bonding refers to hydrogen bonding.

[0026] Figure 7 This is a graph showing the change in relative resistance of the lignin-based conductive self-healing hydrogel prepared in Example 2 over time at different bending angles of finger joints.

[0027] Figure 8 This is a graph showing the change in relative resistance of the lignin-based conductive self-healing hydrogel prepared in Example 2 over time at different bending angles of the wrist joint.

[0028] Fig. 9 This is a graph showing the change in relative resistance of the lignin-based conductive self-healing hydrogel prepared in Example 2 over time at different bending angles of the elbow joint. DETAILED DESCRIPTION

[0029] The technical solutions in the embodiments of the present invention will be described clearly and completely below in combination with the embodiments of the present invention and the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. All other embodiments obtained by ordinary technicians in this field without creative work based on the embodiments of the present invention are within the scope of protection of the present invention.

[0030] Unless otherwise specifically stated, the numerical value set forth in these embodiments does not limit the scope of the present invention. The technology and method known to those of ordinary skill in the relevant art may not be discussed in detail, but in appropriate cases, the technology and method should be considered as a part of the specification. In all examples shown and discussed here, any specific value should be interpreted as being merely exemplary, rather than as a limitation. Therefore, other examples of exemplary embodiments may have different values.

[0031] The experimental methods in the following examples without specifying specific conditions are usually measured according to national standards; if there is no corresponding national standard, it is carried out according to the general international standards or the standard requirements proposed by relevant enterprises. Unless otherwise specified, all parts are by weight and all percentages are by weight.

[0032] Example 1

[0033] A method for preparing a lignin-based conductive self-healing hydrogel comprises the following steps:

[0034] 0.05 g of cyclodextrin (β-cd) and 0.025 g of alkali lignin were added to a 0.8 wt % borax aqueous solution (containing 4.775 g of borax), and the mixture was placed in a 90° C. oil bath, heated and stirred until the β-cd and alkali lignin were uniformly dissolved; 0.15 g of PVA was added under magnetic stirring at room temperature to uniformly disperse and prevent agglomeration, and the mixture was placed in a 90° C. oil bath and magnetically stirred until the PVA was uniformly dissolved to form a uniform mixed material, and the pH value of the mixed material was adjusted to 9.2 to obtain a viscous material;

[0035] The mixture was frozen at 0°C for 12 h and then thawed to room temperature to obtain a uniform and stable lignin-based conductive self-healing hydrogel. The hydrogel product in this example was recorded as 0.5% LCP.

[0036] The cross section of the hydrogel obtained in this example was observed by SEM. The result showed that the LCP hydrogel in this example was connected in a three-dimensional network structure in the cross section, and the pore structure was densely and evenly distributed.

[0037] The hydrogel obtained in this example was tested by infrared spectroscopy, and the peak positions of the characteristic peaks indicated that PVA, β-CD, alkali lignin and borate ions were successfully complexed to form a physically cross-linked hydrogel.

[0038] Example 2

[0039] A method for preparing a lignin-based conductive self-healing hydrogel comprises the following steps:

[0040] 0.05 g of cyclodextrin (β-cd) and 0.05 g of alkali lignin were added to a 0.8 wt % borax aqueous solution (containing 4.75 g of borax), and the mixture was placed in a 90° C. oil bath for heating and stirring until the β-cd and alkali lignin were uniformly dissolved; 0.15 g of PVA was added under magnetic stirring at room temperature to uniformly disperse and prevent agglomeration, and the mixture was placed in a 90° C. oil bath for magnetic stirring until the PVA was uniformly dissolved to form a uniform mixed material, and the pH value of the mixed material was adjusted to 9.2 to obtain a viscous material;

[0041] The hydrogel was frozen at 0°C for 12 h and then thawed to room temperature to obtain a uniform and stable lignin-based conductive self-healing hydrogel. The hydrogel product in this example is recorded as 1% LCP.

[0042] The cross section of the hydrogel obtained in this example was observed by SEM, and the results were as follows: Figure 2 As shown by Figure 2 It can be seen that the LCP hydrogel of this embodiment is connected in a three-dimensional network structure in the cross section, and the pore structure is densely and evenly distributed.

[0043] Example 3

[0044] A method for preparing a lignin-based conductive self-healing hydrogel comprises the following steps:

[0045] 0.05 g of cyclodextrin (β-cd) and 0.15 g of alkali lignin were added to a 0.8 wt % borax aqueous solution (containing 4.65 g of borax), and the mixture was placed in a 90° C. oil bath for heating and stirring until the β-cd and alkali lignin were uniformly dissolved; 0.15 g of PVA was added under magnetic stirring at room temperature to uniformly disperse and prevent agglomeration, and the mixture was placed in a 90° C. oil bath for magnetic stirring until the PVA was uniformly dissolved to form a uniform mixed material, and the pH value of the mixed material was adjusted to 9.2 to obtain a viscous material;

[0046] The hydrogel was frozen at 0°C for 12 h and then thawed to room temperature to obtain a uniform and stable lignin-based conductive self-healing hydrogel. The hydrogel product in this example is recorded as 3%-LCP.

[0047] The cross section of the hydrogel obtained in this example was observed by SEM. The result showed that the LCP hydrogel in this example was connected in a three-dimensional network structure in the cross section, and the pore structure was densely and evenly distributed.

[0048] The hydrogel obtained in this example was tested by infrared spectroscopy, and the peak positions of the characteristic peaks indicated that PVA, β-CD, alkali lignin and borate ions were successfully complexed to form a physically cross-linked hydrogel.

[0049] Example 4

[0050] The preparation of the lignin-based conductive self-healing hydrogel in this embodiment is the same as that in Example 2, except that the cyclodextrin used is α-cyclodextrin; the pH value of the mixture is adjusted to 8.5; and the freezing treatment temperature is -20°C.

[0051] The cross section of the hydrogel obtained in this example was observed by SEM. The result showed that the LCP hydrogel in this example was connected in a three-dimensional network structure in the cross section, and the pore structure was densely and evenly distributed.

[0052] The hydrogel obtained in this example was tested by infrared spectroscopy, and the peak positions of the characteristic peaks indicated that PVA, β-CD, alkali lignin and borate ions were successfully complexed to form a physically cross-linked hydrogel.

[0053] Example 5

[0054] The preparation of the lignin-based conductive self-healing hydrogel in this embodiment is the same as that in Example 2, except that the cyclodextrin used is γ-cyclodextrin; the pH value of the mixed material is adjusted to 10, and the freezing treatment temperature is -10°C.

[0055] The cross section of the hydrogel obtained in this example was observed by SEM. The result showed that the LCP hydrogel in this example was connected in a three-dimensional network structure in the cross section, and the pore structure was densely and evenly distributed.

[0056] The hydrogel obtained in this example was tested by infrared spectroscopy, and the peak positions of the characteristic peaks indicated that PVA, β-CD, alkali lignin and borate ions were successfully complexed to form a physically cross-linked hydrogel.

[0057] Comparative Example 1

[0058] The hydrogel of this comparative example is a blank control, in which lignin and cyclodextrin are not present, and other conditions are the same as those in Example 1. The hydrogel product of this comparative example is recorded as CP.

[0059] Comparative Example 2

[0060] The preparation of the hydrogel in this comparative example is the same as that in Example 1, except that no lignin is contained, and the obtained hydrogel product is recorded as 0% LCP.

[0061] The 1% LCP hydrogel of Example 2, the CP hydrogel of Comparative Example 1, the 0% LCP hydrogel of Comparative Example 2, and the raw materials PVA, β-cyclodextrin powder, and alkali lignin powder were subjected to infrared spectroscopy testing. The infrared spectra are shown in FIG. Figure 1 As shown, 1% LCP represents the product of Example 2, 0% LCP represents the product of Comparative Example 2, CP represents the product of Comparative Example 1, AL powder represents the raw material alkali lignin powder, PVA powder represents the raw material PVA powder, and β-CD powder represents the raw material β-cyclodextrin. Figure 1 It can be seen that the 3449cm of the AL powder, β-CD powder and PVA powder curves -1 Significantly shifted to 3345cm for CP, 0% LCP, and 1% LCP -1 This indicates that hydrogen bonds may be formed between the hydroxyl groups of alkali lignin, PVA, and β-CD. The infrared curve of the LCP hydrogel in Example 2 is at 1050 cm -1 The CO stretching vibration of β-CD is at 1515 cm -1 、1425cm -1 and 1600cm -1 There is aromatic skeleton vibration of lignin at 1375cm -1 The stretching vibration of aliphatic CH and phenolic hydroxyl groups of lignin is at 661 cm-1 The BOB bond in the borate network is bent at 833 cm -1 There is a BO bond (by the residual B(OH) 4 - stretched), at 1333cm -1 The peaks at the positions (new absorption peaks) have asymmetric stretching relaxation characteristic peaks of BOC (which corresponds to the cross-linking structure formed by borate and hydroxyl groups). The characteristic peaks at these positions confirm the presence of borax and boric acid. These results indicate that PVA, β-CD, alkali lignin and borate ions are successfully complexed to form a physically cross-linked hydrogel.

[0062] The hydrogels of Examples 1-3 and Comparative Examples 1 and 2 were subjected to stress tests at 25°C to detect the viscoelasticity of the hydrogels. The isothermal frequency scanning curves are shown in FIG. Figure 3 As shown in Figure , the storage modulus (G') corresponds to the elasticity of the hydrogel, and the loss modulus (G") corresponds to the viscosity of the hydrogel. Figure 3 It can be seen that the storage modulus (G') of the hydrogels prepared in Examples 1-3 of the present invention and Comparative Examples 1 and 2 is much greater than the loss modulus (G"), which indicates that they have typical hydrogel properties.

[0063] The above hydrogels of the embodiments and comparative examples were tested for performance, and the results are shown in Table 1.

[0064] The tensile performance test is to stretch a hydrogel sample with a size of 20 mm × 5 mm × 5 mm (length × width × height) from both ends until it breaks, record the final length, and calculate the elongation rate.

[0065] The self-healing performance test is to cut the formed hydrogel in the middle with a sharp blade, put the cut sections into contact, and test the time it takes for the hydrogel to completely heal and return to its original shape without any external stimulation.

[0066] The conductivity test is to clamp the cylindrical hydrogel on the battery test frame fixture, connect it to the electrochemical workstation with a wire, measure the impedance of the hydrogel, and then calculate the conductivity according to the following formula:

[0067]

[0068] Where σ is the conductivity, d is the hydrogel thickness, A is the hydrogel cross-sectional area, and R is the hydrogel impedance.

[0069] Table 1 Hydrogel properties of examples and comparative examples

[0070]

[0071] As shown in Table 1, compared with Comparative Example 2, after adding alkali lignin, the elongation and conductivity of the LCP hydrogel in the present invention are significantly improved, and the self-healing time is further shortened. As the content of alkali lignin increases, the elongation of the LCP hydrogel increases continuously, and the maximum elongation can be stretched to 2000% of its own length (the actual picture of 1% LCP after stretching is shown in Figure 1). Figure 4 The conductivity also increased continuously, reaching a maximum of 0.70771 S / m, and the self-healing time reached a minimum of 8 s in Example 2. Compared with Example 1, the addition of cyclodextrin in Comparative Example 2 can improve the mechanical properties of the hydrogel, and the elongation, conductivity and self-healing properties of the hydrogel are more significantly improved by α-CD, γ-CD and β-CD.

[0072] The time-healing efficiency curve of the lignin-based conductive self-healing hydrogel from cut to healed state in Example 2 is as follows Figure 5 As shown by Figure 5 It can be seen that the hydrogel of the present invention can quickly recover to its original shape within 8 seconds after being cut, and has a high self-healing efficiency.

[0073] The sensing diagram of the lignin-based conductive self-healing hydrogel in Example 2 is as follows: Figure 7-Figure 9 As shown, Figure 7-Figure 9 The graphs are respectively the curves of the relative resistance of the hydrogel to different bending angles of the finger joints, wrist joints, and elbow joints over time. Figure 7-Figure 9 It can be seen that when the bending angle of the finger joint changes from 0° to 90°, the resistance of the hydrogel sensor gradually increases, indicating that the change in the relative resistance of the hydrogel sensor can flexibly and in real time respond to the bending activity of the finger. At different bending angles of the wrist and elbow joints, the resistance of both also changes significantly: when the hydrogel sensor is stimulated by stretching or bending, the relative resistance of the hydrogel sensor increases, and when the stimulation disappears, the hydrogel sensor returns to its original relative resistance, which indicates that the hydrogel of the present invention responds quickly and reversibly to large limb movements of the wrist and elbow joints.

[0074] The mechanism of the lignin-based conductive self-healing hydrogel formed by the present invention is as follows Figure 6 As shown, Figure 6Taking β-CD as an example, β-CD and PVA polymers form a basic skeleton with borax through mutual hydrogen bonding and physical cross-linking. β-CD and PVA polymer form a linear interaction, which makes the β-CD line wear block polymer and improves the stability of the polymer. Alkali lignin rich in phenolic hydroxyl, alcoholic hydroxyl and carboxyl groups has high tensile properties. The uniform distribution of lignin can form dynamic hydrogen bonds with β-CD and PVA, and cross-link with boric acid, reducing the interaction and entanglement between PVA and PVA, PVA and β-CD, β-CD and β-CD polymer chains, and improving the viscoelasticity, tensile properties and self-healing ability of LCP hydrogel. After adding an appropriate amount of alkali lignin, the tensile strength of LCP hydrogel is 20 times that of the initial hydrogel, and with the increase of alkali lignin content, the π-π superposition effect is more obvious, which increases the conductivity. When the amount of lignin added is too large, the large number of hydrogen bonds between lignin and β-CD or PVA and the dynamic hydrogen bonds of boric acid limit the free flow of polymer molecular chains, which will lead to a decrease in the storage modulus and elongation of LCP hydrogel. Therefore, a lignin content of less than 3wt% is more appropriate.

[0075] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a lignin-based conductive self-healing hydrogel, characterized in that: The steps include: The cyclodextrin, alkaline lignin and polyvinyl alcohol are uniformly dissolved in a borax aqueous solution to form a uniform mixture, and then the pH value is adjusted to be alkaline to obtain a viscous material, which is then frozen and thawed to room temperature to finally obtain a uniform and stable lignin-based conductive self-healing hydrogel; The mass ratio of the cyclodextrin, the alkali lignin, the polyvinyl alcohol and the borax is 1:(0.5-3):3:(90-100).

2. The method for preparing a lignin-based conductive self-healing hydrogel according to claim 1, characterized in that: The cyclodextrin is one or more of α-cyclodextrin, β-cyclodextrin and γ-cyclodextrin; the molecular weight of the polyvinyl alcohol is 15,000-20,000; and the mass concentration of the borax aqueous solution is 0.5-2%.

3. The method for preparing a lignin-based conductive self-healing hydrogel according to claim 1, characterized in that: Adjusting the pH value to be alkaline means adjusting the pH value of the mixed material to 8-10.

4. The method for preparing a lignin-based conductive self-healing hydrogel according to claim 1, characterized in that: The freezing treatment temperature is -20 to 10°C and the treatment time is 12 hours.

5. A lignin-based conductive self-healing hydrogel prepared according to the preparation method according to any one of claims 1 to 4.

6. Application of the lignin-based conductive self-healing hydrogel prepared by the preparation method according to any one of claims 1 to 4 in wearable electronic sensors, characterized in that: Wearable electronic sensors for fingers, wrists, and elbows.

Citation Information

Patent Citations

  • Preparation method of nanocellulose / borax / polyvinyl alcohol self-healing hydrogel

    CN110655744A

  • Ultrafast self-healing polysaccharide-based hydrogel strain sensor and manufacturing method thereof

    CN112066866A